Molecular docking study of L-Asparaginase I from Vibrio campbellii in the treatment of acute lymphoblastic leukemia (ALL) - Mohideen Abdul Khader Sultan (The EuroBiotech Journal, 2020)
The potential use of asparaginases has gained tremendous significance in the treatment of acute lymphoblastic leukemia (ALL). Earlier studies suggest L-asparaginases (L-ASP) extracted from Escherichia coli and Erwinia aroideae regulates L-asparagine (L-Asn) from the circulating blood. Prolonged exposure to these enzymes may lead to hypersensitivity reactions. So, it is important to find novel asparaginases with anti-cancer properties. The three-dimensional structure of L-ASP I from Vibrio campbellii was determined by homology modeling using EasyModeller v.4.0. The structure was validated with quality indexing tools and was deposited in Protein Model DataBase. Molecular docking was performed between L-ASP I and ligand substrate L-Asn to study enzyme-substrate interactions. Qualitative and quantitative analysis of L-ASP I enzyme was found to be reliable and stable with a significant protein quality factor (LG score: 7.129). The enzyme is a dimer, belongs to α/β class of proteins. The active sites comprises of N-glycosylation site and a catalytic triad (T14-S117-D92). The binding energy of the docked complex was calculated to be -7.45 kcal/mol. The amino acid T14 identified as a primary nucleophile essential for catalytic reaction. The enzyme L-ASP I of V. campbellii provides a detailed view of structure and functional aspects with ligand substrate L-Asn. This in silico investigation has explicitly demonstrated for the first time that cytosolic L-ASP Type I of V. campbellii to have a catalytic triad which was attributed only to periplasmic L-ASP Type II. Thus, L-ASP I can serve as anti-leukemic agent in the treatment, management and control of ALL.